2017
DOI: 10.1021/acscentsci.7b00159
|View full text |Cite
|
Sign up to set email alerts
|

A General Small-Scale Reactor To Enable Standardization and Acceleration of Photocatalytic Reactions

Abstract: Photocatalysis for organic synthesis has experienced an exponential growth in the past 10 years. However, the variety of experimental procedures that have been reported to perform photon-based catalyst excitation has hampered the establishment of general protocols to convert visible light into chemical energy. To address this issue, we have designed an integrated photoreactor for enhanced photon capture and catalyst excitation. Moreover, the evaluation of this new reactor in eight photocatalytic transformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
207
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 226 publications
(217 citation statements)
references
References 29 publications
6
207
0
4
Order By: Relevance
“…Recently, irradiation conditions have been shown to be key optimization parameters for small molecule reactions mediated by a variety of photocatalysts. 35 For photoinduced O-ATRP, the photoexcitation process controls the efficiency of activation directly and the efficiency of deactivation indirectly. The characteristics of absorption (PC → PC*), quantum yield, excited-state lifetime, and reduction potential of 3 PC* are major factors in the efficiency of the polymerization catalytic cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, irradiation conditions have been shown to be key optimization parameters for small molecule reactions mediated by a variety of photocatalysts. 35 For photoinduced O-ATRP, the photoexcitation process controls the efficiency of activation directly and the efficiency of deactivation indirectly. The characteristics of absorption (PC → PC*), quantum yield, excited-state lifetime, and reduction potential of 3 PC* are major factors in the efficiency of the polymerization catalytic cycle.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Hesitation may arise from various considerations,f or example,f rom uncertainties regarding the multitude of reported photochemical setups. [9] As photochemistry is not yet fully established within the mainstream synthetic community and fundamentally very different setups are available,there is an eed to ensure confidence in photochemistry.Asimpler approach could allow the parameters of existing setups to be more clearly defined and controlled, two issues known to hamper reproducibility. [9] As photochemistry is not yet fully established within the mainstream synthetic community and fundamentally very different setups are available,there is an eed to ensure confidence in photochemistry.Asimpler approach could allow the parameters of existing setups to be more clearly defined and controlled, two issues known to hamper reproducibility.…”
mentioning
confidence: 99%
“…2B, right). Under the dilute micromolar conditions (using ~4.4 equivalents of T 2 O), we observed that the use of 11 in its free base form—along with increased loadings of the photo-redox (4 mol %) and thiol (60 mol %) catalysts—and the use of the integrated photoreactor developed at Merck & Co., Inc. (41), as the visible light source greatly enhanced the incorporation of tritium, yielding [ 3 H ] 11 with a high specific activity of 40.2 Ci mmol −1 and an isolated yield of 39.8 mCi (Fig. 2B, right).…”
mentioning
confidence: 97%